Teachers’ Perception of Online Learning during Pandemic Covid-19 - Rahayu, Retno Puji; Wirza, Yanty (Universitas Pendidikan Indonesia, 2020)
Since March 2020, the case of coronavirus disease or known as Covid-19, has become a global pandemic. According to UNESCO, schools are closed in about 100 countries due to a public health emergency, including Indonesia. The condition forces teachers to make the transition of the way they teach from face to face learning to online learning. This study investigated EFL teachers’ Perception of online English language learning. Their perceptions were analyzed in three aspects: perceived usefulness, perceived ease of use, and their attitude toward online English language learning. This study employed a descriptive design with a qualitative approach. A survey questionnaire and interview were used in this study to elicit the responses of 102 Junior High School English teachers in Bandung. This study's findings revealed that the participants showed a positive perception of the usefulness and ease of use of online learning systems during pandemic Covid-19. Still, more than half of the teachers didn’t agree on the effectiveness of it. Even though the teachers face many online teaching problems, they could show the right attitude toward using technology to teach online.